Customizing local and systemic therapies for women with early breast cancer: the St. Gallen International Consensus Guidelines for treatment of early breast cancer 2021 - Burstein, H J; Curigliano, G; Thürlimann, B; Weber, W P; Poortmans, P; Regan, M M; Senn, H J; Winer, E P; Gnant, M (Annals of oncology, 2021)
The 17th St Gallen International Breast Cancer Consensus Conference in 2021 was held virtually, owing to the global COVID-19 pandemic. More than 3300 participants took part in this important bi-annual critical review of the 'state of the art' in the multidisciplinary care of early-stage breast cancer. Seventy-four expert panelists (see Appendix 1) from all continents discussed and commented on the previously elaborated consensus questions, as well as many key questions on early breast cancer diagnosis and treatment asked by the audience. The theme of this year's conference was 'Customizing local and systemic therapies.' A well-organized program of pre-recorded symposia, live panel discussions and real-time panel voting results drew a worldwide audience of thousands, reflecting the far-reaching impact of breast cancer on every continent. The interactive technology platform allowed, for the first time, audience members to ask direct questions to panelists, and to weigh in with their own vote on several key panel questions. A hallmark of this meeting was to focus on customized recommendations for treatment of early-stage breast cancer. There is increasing recognition that the care of a breast cancer patient depends on highly individualized clinical features, including the stage at presentation, the biological subset of breast cancer, the genetic factors that may underlie breast cancer risk, the genomic signatures that inform treatment recommendations, the extent of response before surgery in patients who receive neoadjuvant therapy, and patient preferences. This customized approach to treatment requires integration of clinical care between patients and radiology, pathology, genetics, and surgical, medical and radiation oncology providers. It also requires a dynamic response from clinicians as they encounter accumulating clinical information at the time of diagnosis and then serially with each step in the treatment plan and follow-up, reflecting patient experiences and treatment response.